(untitled) (diségno, 2024)
Between 1928 and 1929, Sigurd Lewerentz designed and built Theodor Anton Bergen’s tomb on the islet Utterö, in an archipelago near Stockholm that can only be reached by boat. There are three known versions of the project [1]. The well-known sketches of the first two belong to the category of inquiries into architectural graphic representation. They are plans, elevations, sections and axonometries, typical of the architectural language with which the author is defining the program and the proposal of an implantation, at the same time as he is approaching the dimensioning of his intervention. [read more]